Applied Psychology - Davey, Graham (Bps Blackwell, 2011)
This is a valuable book for those studying applied psychology. The Coverage of professional roles, how psychological concepts permeate practice, and its overall breadth and skillful blend of evidence, theory and professional issues make it a front runner. Preface, Introduction, Clinical Psychology, Health Psychology, Forensic Psychology, Educational Psychology, Occupational Psychology, Sports and Exercise Psychology, Glossary, Index.